Mild myopathy is associated with COMP but not MATN3 mutations in mouse models of genetic skeletal diseases. - Katarzyna A Piróg; Yoshihisa Katakura; Aleksandr Mironov; Michael D Briggs (PLoS ONE)
Pseudoachondroplasia (PSACH) and multiple epiphyseal dysplasia (MED) are skeletal disorders resulting from mutations in COMP, matrilin-3 or collagen IX and are characterised by short-limbed dwarfism and premature osteoarthritis. Interestingly, recent reports suggest patients can also manifest with muscle weakness. Here we present a detailed analysis of two mouse models of the PSACH/MED disease spectrum; ΔD469 T3-COMP (PSACH) and V194D matrilin-3 (MED). In grip test experiments T3-COMP mice were weaker than wild-type littermates, whereas V194D mice behaved as controls, confirming that short-limbed dwarfism alone does not contribute to PSACH/MED-related muscle weakness. Muscles from T3-COMP mice showed an increase in centronuclear fibers at the myotendinous junction. T3-COMP tendons became more lax in cyclic testing and showed thicker collagen fibers when compared with wild-type tissue; matrilin-3 mutant tissues were indistinguishable from controls. This comprehensive study of the myopathy associated with PSACH/MED mutations enables a better understanding of the disease progression, confirms that it is genotype specific and that the limb weakness originates from muscle and tendon pathology rather than short-limbed dwarfism itself. Since some patients are primarily diagnosed with neuromuscular symptoms, this study will facilitate better awareness of the differential diagnoses that might be associated with the PSACH/MED spectrum and subsequent care of PSACH/MED patients.